Usulan Perancangan Ulang Tata Letak Workshop Produksi Spun Pile PT. Xyz Menggunakan Metode Systematic Layout Planning (SLP) dan Metode Grafik - Beverly Jessa Surentu; Radhinka Mahsa Aziza; Militya Christy Emmanuela Melale; Tiaradia Ihsan (SENTRI: Jurnal Riset Ilmiah, 2026)
Facility layout design plays an important role in improving material flow efficiency in production systems. The spun pile production workshop at PT. XYZ involves sequential processes and large, heavy materials, while the existing layout has not fully considered process sequence and material handling intensity, resulting in long material handling distances and Work in Process (WIP) accumulation. This study aims to redesign the facility layout of the spun pile production workshop at PT. XYZ using Systematic Layout Planning (SLP) and the Graph Method, and to compare the effectiveness of both methods. A descriptive quantitative approach was employed using data on facility dimensions, workstation positions, and material flow. Data analysis included evaluation of the existing layout, development of ARC, FTC, TCR, and ARD. The results show that the SLP-based layout produces a total material handling distance of 5,415.86, which is lower than the graph method layout 5,431.16 and the existing layout 5,473. Therefore, the SLP method is considered more effective in improving material flow efficiency at PT. XYZ.